High Performance Catalysts For Storage And Reduction Of NOx In Diesel Engine Exhaust. - Abdullah, Ahmad Zuhairi; Bhatia, Subhash (2005)
Diesel engines offer fuel eficiency and reliability in its operation but they also cause many adverse environmental effects, especially due to the emission of nitrogen oxides (NOx) ana particulate matter in the form of soot.